(untitled) (Polifonia, 1997)
ABSTRACT: In the years of colonization that preceded the 19th. century, the Portuguese language spoken in Brazil was undergoing transformations and becoming an idiom very different from the one spoken and written in Portugal. It is an unquestionable fact that the linguistic diversity became the theme of never ending debates between the separatists (men of romantic "humor") and legitimists (men of classic "humor"). The former, soaked in the realm of ideas of liberty, saw the linguistic differentiation between Brazil and Portugal as positive, and wanted to hasten the course of the distinction. The later, "Guardians of the vernacular", viewed this differentiation as negative and wanted to halt its progress. Based on Michel Foucault’s theory of the enunciation, we have tried to approach the debate from inside the discourse of the separatists.